What flies in the far south of Croatia? The diversity of Rhopalocera in the Konavle region, southern Dalmatia (Lepidoptera: Papilionoidea) - Koren, Toni; Martinović, Matea; Dender, Dubravko (SHILAP Revista de lepidopterología, 2025)
This research explores the diversity of Rhopalocera in the Konavle region, the southernmost part of Dalmatia. A total of 106 species were recorded, the majority of which were documented for the first time in this area due to the scarcity of previous surveys. Zoogeographical analysis indicated a high proportion of Euro-Siberian and Euro-Oriental species, with significant contributions from Holarctic and Mediterranean species. Compared to the surrounding areas in Bosnia and Herzegovina and Montenegro, between Trebinje and Mt. Orjen, a greater diversity of Rhopalocera was observed, with a Sorensen similarity index of 0.39, indicating a relatively distinct fauna. Most of the studied area falls within the Natura 2000 ecological network, where all species were recorded, including nearly all sites of conservation value based on the abundance of endangered species and species listed in the Habitats Directive. The northern part of the study area belongs to the Sniježnica mountain, which has been separately analysed, with 103 species recorded so far, more than on smaller mountains such as Mosor and Kozjak but fewer than larger and significantly higher mountains like Biokovo, Svilaja, and Dinara. Many interesting species were recorded during this survey and the presence of several of them was discussed in greater detail. Notes about the conservation of Rhopalocera in the surveyed areas are provided.